Mark Twain and human nature - Quirk, Tom, 1946- (Mark Twain and his circle series., 2007)
"Explores Mark Twain's works--including The Innocents Abroad, Following the Equator, The Adventures of Tom Sawyer, Adventures of Huckleberry Finn, Puddin' Head Wilson, and What Is Man?--in terms of his interest in the subject of human nature, examining how his outlook on the human condition changed over the years"--Provided by publisher